Geoproduct potential analysis based on the example of the GEOsfera Ecological and Geological Education Center in Jaworzno - Bieniek, Barbara; Kordysh, Alina; Mirosławski, Mateusz; Nowak, Katarzyna; Sękowski, Kacper; Sierka, Edyta (Geotourism/Geoturystyka, 2021)
At the time of discovering and exposing the scientific and educational potential of areas where mineral resources were exploited in the past, they have become a significant element in tourism elements. In the presented paper, the potential of the GEOsfera Ecological and Geological Education Centre in Jaworzno as a geoproduct was analysed. In the first part of the study, based on the published works and consultations with experts, the “geoproduct” was defined. Then the area, where the GEOsphere is located, was characterized. Its geology, the natural world, the way of land development and the promotion of geo-attractions located in this area are described. In the next stage, an analysis of the opinions of users regarding their perception of the GEOsphere was carried out. For this purpose, evaluations posted on social media and the collected survey results were used. As shown by the results, the majority of users of the GEOsfera are residents of Jaworzno – 63% of the respondents. The importance of the GEOsphere as an educational centre was indicated by 22% of visitors. About 5% of the respondents mentioned learning and obtaining information from the descriptions placed next to the exhibits in the centre. 93% of respondents recognised the graduation tower as the greatest attraction of the GEOsphere. Over 92% of people noticed the recreational role of the GEOsphere. 81% of users declared that they were satisfied with their visit to the GEOsphere. More than half of the respondents (56%) visited the GEOsfera with their family. A significant part of respondents (42%), pointed to the role of environmental protection, which is extremely important from the point of view of geoproducts’ design. The respondents also indicated that the GEOsphere has numerous geological, natural and educational functions and protects and promotes the geological heritage of the region.